ANALISIS NILAI TAMBAH (VALUE ADDED) AGROINDUSTRI PEMINDANGAN IKAN DI KELURAHAN BINTARO KECAMATAN AMPENAN KOTA MATARAM - MARINI, IDA AYU KETUT; ARTIKA, IDA BAGUS EKA (Universitas Mahasaraswati K. Mataram, 2024)
Fresh fish has a perishable nature (Perishable food) requires a processing process so that it has a longer shelf life, is easier to distribute, and is easier to consume. Marinating is a processing and preservation technique by boiling or cooking fish in salted conditions for a period of time. certain conditions in a container and then the process of reducing the water content to a certain limit occurs. This research is entitled